A rare case of carcinoid tumor in a tailgut cyst - Asad Jehangir; Brian H. Le; Frank M Carter (Journal of Community Hospital Internal Medicine Perspectives, 2016)
Tailgut cysts are rare congenital lesions that arise from the failure of regression of the embryological tailgut. We report a case of neoplastic transformation of tailgut cyst to carcinoid tumor which is exceedingly uncommon.